Condições de estresse e conforto térmico em fábrica de pré-moldado em Ponta Grossa - PR - Galvan, Tanise Fuckner de Oliveira (2018)
Heat stress is a recognized risk that workers in various industries are exposed. In order to verify the stress condition and also thermal comfort in the precast concrete factory, a research was carried out in which the environmental and personal variables were obtained through measurements and questionnaires. The preliminary evaluation of the heat stress was performed by the HSSI scale, which indicated the absence of heat stress in this factory. To confirm this conclusion, the evaluation of the environment was carried out through the IBUTG and PHS indices, which confirmed the absence of heat stress. As there was no incidence of heat stress, the environment was evaluated with respect to thermal comfort, in the measurements in which the PMV index was applicable and the PET index was calculated. Through the calculation of the PMV index, it was verified that in only one measurement the environment can be considered comfortable, in the others the environment is considered to be thermally uncomfortable. Through the calculation of the PMV index, it was verified that in only one measurement the environment can be considered comfortable, in the others the environment is considered to be thermally uncomfortable. The results of the PET index show that thermal discomfort was also characterized in most of the measurements.